LINTASAN BELAJAR GEOMETRI TRANSFORMASI DENGAN MENGGUNAKAN KONTEKS KAIN BUNA - Talisadika Serrisanti Maifa; Cecilia Novianti Salsinha; Hendrika Bete (HISTOGRAM: Jurnal Pendidikan Matematika, 2020)
This study is aimed to design a mathematics learning trajectory in geometry transformation using Buna Woven Fabric as a context in the learning process with the Indonesian Realistic Mathematics Education (RME)  approach. This study is a a design research that contains three stages, preliminary design, teaching experiment, and retrospective analysis. The result of this research is the learning trajectory design of geometry transformation especially Reflection using Buna woven fabric. The design consists of four activities, namely, drawing woven fabric patterns, copying woven fabric patterns, finding the image of transformation, and finding the formula of reflection . The results indicated the learning trajectory can stimulate students to understand  the concept of geometry transformation.